Tackling food insecurity and malnutrition in Ethiopia through diversification - International Potato Center (2012)
Sweetpotato is ideally suited as a post-emergency rehabilitation crop in Ethiopia. Progress in being made in introducing pro-vitamin A rich sweetpotato in Tigray, where sweetpotato is a brand new crop as well as in SNNPR, the region with the highest sweetpotato production in Ethiopia.